Evaluation and Optimization Strategies for Provincial Culture and Tourism Integration from the Perspective of Landscape Narrative: A Case Study of Anhui Province, China - Yunxi Hong; Li Tu; Minghe Wan (Land)
Landscape narrative theory, which focuses on the interaction between space, culture, and human experience, provides a practical and interdisciplinary framework for guiding the integration of culture and tourism. By incorporating storytelling elements into tourism planning, it helps transform static cultural assets into engaging visitor experiences. This approach is particularly relevant in provincial contexts where cultural resources are unevenly distributed. Taking Anhui Province, China, as a case study, this research builds a five-dimensional evaluation system covering culture–tourism economy, cultural resources, tourism resources, transportation accessibility, and policy support. Using spatial analytical methods such as Moran’s I and the Spatial Autoregressive (SAR) model, the study identifies clear spatial clustering patterns and influential factors. The SAR model results show that transportation accessibility (coefficient = 0.685, p < 0.01) and policy support (coefficient = 0.736, p < 0.01) significantly promote integration. In contrast, cultural resources (coefficient = −0.352, p < 0.01) and tourism resources (p ≈ 0.11) have limited or no significant direct economic impact. Based on these findings, this paper proposes targeted strategies such as building regional narrative networks, enhancing infrastructure and policy coordination, and fostering collaborative development. The key contribution of this study lies in applying landscape narrative theory at the provincial level to construct a “Theory–Indicators–Method–Strategy” framework, offering new perspectives for promoting high-quality regional culture–tourism integration.